The implementation of culturally responsive teaching in ELT classrooms within the concept of emancipated curriculum - Agil Fitriya Hidayati; Yuliati Yuliati; Fonny Dameaty Hutagalung (ELT Forum: Journal of English Language Teaching, 2024)
This qualitative study explores the importance of implementing Culturally Responsive Teaching (CRT) in English Language Teaching (ELT) classes in Indonesian higher education under the Emancipated Curriculum framework. In this qualitative study, the Emancipated Curriculum framework is used to explore the importance and urgently needed need of introducing Culturally Responsive Teaching (CRT) into English Language Teaching (ELT) programs in Indonesian higher education. The study emphasizes the important role of learner-centered strategies in developing students' critical thinking abilities and promoting independence by implementing the advancement of social justice, critical thinking, and student empowerment. In order to improve cultural responsiveness in ELT, it emphasizes the critical necessity of coherence between instructional practices and policies. It also advocates for curriculum design and pedagogical approach adaptation in order to create inclusive and empowering learning environments that meet the diverse needs of students. The results highlight the need to implement culturally responsive teaching strategies into the curriculum to address current concerns about equity and inclusivity. This research provides insightful information for teachers and administrators who would like to encourage inclusive, hospitable ELT classrooms that value diversity. This study is a valuable resource for educators who want to build learning environments that empower and accept students from all cultural origins, thereby encouraging more equity and inclusivity in Indonesian education.